Transformasi Kapasitas Kepemimpinan Perempuan Melalui Penguatan Komunikasi Asertif dan Manajemen Prioritas Berbasis Literasi Domestik - Regina Regina; Risma Niswaty; Andi Putri Tenriyola; Fahmi Surya Abdi; Tenriwaru Tenriwaru (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This community service activity was carried out in response to the phenomenon of double burden experienced by women, especially mothers in Makassar City, who are required to carry out domestic and public roles simultaneously. This condition often causes women's leadership capacity and managerial abilities to be underrecognized. This service aims to transform the mindset of participants from just survival to empowered mothers through strengthening assertive speaking skills and priority management. The method used is Service-Learning with a participatory approach which is implemented through five stages of 120-minute workshops, including emotional validation, experiential reflection, role audit, identification of leadership skills, and simulation of Glass Ball and Rubber Ball strategies in decision-making. The results of the activity showed an increase in participants' critical awareness in recognizing leadership competencies and managerial skills possessed through domestic activities. In addition, participants showed behavioral changes in determining priorities and making decisions more effectively. The expected long-term impact is the formation of a supportive community and the strengthening of women's leadership that is able to balance the roles of family and society in harmony.